Screening, diagnosis, treatment and outcomes of developmental dysplasia of the hip in Brazilian population: a scoping review - Emily Schaeffer; Patricia Moreno Grangeiro; Patrícia Eduarda Conrado Martins Rocha Jaleca; Sheila Lam; Sana Arora; Daniel Frank Liggio (BMJ Open)
Objective This study aims to map the literature on screening, diagnosis, treatment and outcomes of developmental dysplasia of the hip (DDH) in the Brazilian population aged 0–18 years, to describe regional variations in its presentation and management.Design Scoping review.Data sources PubMed/MEDLINE, Web of Science, Scopus, “Biblioteca Virtual em Saúde” and “Biblioteca Digital Brasileira de Teses e Dissertações”. The journals, Revista Brasileira Ortopedia and Acta Ortopédica Brasileira, were manually searched for non-indexed issues. Databases were searched from their inception to February 2024.Eligibility criteria This scoping review included studies on Brazilian patients aged 0–18 years diagnosed with or being assessed for DDH. No language or date restrictions were applied.Data extraction and synthesis Studies were assessed based on title, authors, publication year, study design, sample size, level of evidence, region of Brazil and healthcare setting (public or private). The articles were then analysed across four categories: screening, diagnosis, treatment and outcomes.Results 52 studies, published between 1951 and 2023, were included. Reported prevalence rates ranged from 0.75 to 56.4 cases per 1000 children. No study examined the effectiveness of specific screening programmes or compared their outcomes. The most common diagnostic methods were the Ortolani manoeuvre and ultrasonography using the Graf method. Of the 27 articles on treatment, 17 focused exclusively on surgical interventions, with the Salter osteotomy being the most frequent procedure.Conclusions There should be a greater focus on understanding the prevalence of DDH in Brazil, the availability of ultrasound devices and trained operators, and the follow-up of conservative treatments. More information on DDH in Brazil is essential for designing and implementing effective screening and treatment programmes. Future research should be done to understand the prevalence of the disease, optimal forms of screening and early treatment.